Longitudinal association between television watching and computer use and risk markers in diabetes in the SEARCH for Diabetes in Youth Study. Issue 5 (12th July 2014) - Li, Chao; Beech, Bettina; Crume, Tessa; D'Agostino, Ralph B; Dabelea, Dana; Kaar, Jill L; Liese, Angela D; Mayer‐Davis, Elizabeth J; Pate, Russell; Pettitt, David J; Taplin, Craig; Rodriguez, Beatriz; et al.
<x xml:space="preserve">Abstract</x> Background The study provides evidence of the longitudinal association between screen time with hemoglobin A1c (HbA1c) and cardiovascular risk markers among youth with type 1 diabetes (T1D) and type 2 diabetes (T2D). Objective To examine the longitudinal relationship of screen time with HbA1c and serum lipids among youth with diabetes. Subjects Youth with T1D and T2D. Methods We followed up 1049 youth (≥10 yr old) with recently diagnosed T1D and T2D participating in the SEARCH for Diabetes in Youth Study. Results Increased television watching on weekdays and during the week over time was associated with larger increases in HbA1c among youth with T1D and T2D (p‐value <0.05). Among youth with T1D, significant longitudinal associations were observed between television watching and TG (p‐value <0.05) (week days and whole week), and low‐density lipoprotein cholesterol (LDL‐c, p‐value <0.05) (whole week). For example, for youth who watched 1 h of television per weekday at the outset and 3 h per weekday 5 yr later, the longitudinal model predicted greater absolute increases in HbA1c (2.19% for T1D and 2.16% for T2D); whereas for youth who watched television 3 h per weekday at the outset and 1 h per weekday 5 yr later, the model predicted lesser absolute increases in HbA1c (2.08% for T1D and 1.06% for T2D). Conclusions Youth with T2D who increased their television watching over time vs. those who decreased it had larger increases in HbA1c over 5 yr. Youth with T1D who increased their television watching over time had increases in LDL‐c, TG, and to a lesser extent HbA1c.